Retraction notice to “Adoption of goat production technology and its impact among rural farmers in nawalparsi district of nepal” [Jurnal Agercolere, 1(1), 1–5] - Krishna Aryal; Bishnu Prasad Kandel (Fakultas Pertanian Universitas Ichsan Gorontalo, 2019)
This article has been retracted: please see Jurnal Agercolere Publication Ethics (http://faperta.unisan.ac.id/jurnal/index.php/jac/ethics). This article has been retracted at the request of the Editor-in-Chief. The author has published manuscripts describing essentially the same research in more than one journal or primary publication, as follow: Aryal, M. Jaishi and A. Gaire, “Adoption of goat production technology and its impact among rural farmers of Nawalparasi district, Nepal” - Nepalese Journal of Agricultural Sciences, 2018, pp. 109–113. ref.6 url: http://www.hicast.edu.np/uploads/colleges/16/5c2a464490dbd.pdf One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.